Moving color : early film, mass culture, modernism - Yumibe, Joshua (Techniques of the moving image., 2012)
Moving Color is the first book-length study of the beginnings of color cinema. It traces the legacy of color history from the beginning of the nineteenth century to the cinema of the early twentieth century and explores the implications of this genealogy on experimental and contemporary digital cinemas.